Radiosynthesis and quality control of [225Ac]AcPSMA-617 for prostate cancer patients by targeted alpha therapy,TAT - Boonkawin, Natphimol; Chotipanich , Chanisa (The Journal of Chulabhorn Royal Academy, 2024)
Background: Specific membrane antigen (PSMA) is a highly expressed transmembrane glycoprotein in prostate cancer cells. The radiolabeling of actinium-225 (225Ac) with such peptide is promising as a good radiotracer for use in targeted alpha therapy among patients with metastatic prostate cancer. In this study, the appropriate methods for [225Ac]AcPSMA-617 labeling and quality control with high yield and radiochemical purity is reported. Methods: The radiolabeling of [225Ac]AcPSMA-617 was prepared by adding the PSMA-617 precursor in ascorbate buffer into the 225Ac solution vail. The ratio of the PSMA-617 peptide and 225Ac activity was optimized to 11.0-19.5:1. The mixed solution in reaction vail was heated at 90°C for 10 min. The labelled [225Ac]AcPSMA-617 solution was formulated by adding 0.1 mg/mL of sodium ascorbate in 0.9%NaCl and ethanol(9:1) 10 mL, then transferred through the 0.22 µm filter to the product vial. The quality control of sterile [225Ac]AcPSMA-617 was performed before patient administration. Results: The average radiosynthesis yield of [225Ac]AcPSMA-617 for 14 times by using the above method was 97.28%±2.87%, with the average radiochemical purity of 96.88%±1.30%. Conclusion: The one step of [225Ac]AcPSMA-617 radiolabeling process provides a high yield of synthesis and radiochemical purity (RCP).